2018
DOI: 10.1101/274258
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrated analysis of human transcriptome data for Rett syndrome finds a network of involved genes

Abstract: (175 words)Rett syndrome (RTT) is a rare disorder causing severe intellectual and physical disability. The cause is a mutation in the gene coding for the methyl-CpG binding protein 2 (MECP2), a multifunctional regulator protein. Purpose of the study was integration and investigation of multiple gene expression profiles in human cells with impaired MECP2 gene to obtain a data-driven insight in downstream effects. Information about changed gene expression was extracted from five previously published studies. We … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…The modules mainly contained interactions from transcription / translation and cell cycle related pathways, which were not found with the classical enrichment analysis. These processes were also previously found in transcriptome pathway analysis of Rett syndrome (Bedogni et al, 2014; Ehrhart et al, 2018). Not surprisingly, the subnetworks do not contain metabolic reactions.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…The modules mainly contained interactions from transcription / translation and cell cycle related pathways, which were not found with the classical enrichment analysis. These processes were also previously found in transcriptome pathway analysis of Rett syndrome (Bedogni et al, 2014; Ehrhart et al, 2018). Not surprisingly, the subnetworks do not contain metabolic reactions.…”
Section: Discussionsupporting
confidence: 71%
“…As expected, our pathway and GO analysis revealed a substantial number of immune system related pathways to be affected in Rett syndrome frontal and temporal cortex tissue samples. Inflammatory processes have been identified previously in Rett syndrome patients, mouse models and in vitro systems, and are suspected to contribute to the development of Rett syndrome (De Felice et al, 2016; Ehrhart et al, 2018). Figure 2 shows many of affected pathways in both frontal and temporal cortex, with similar results found by GO analysis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The severity of the disorder is related to the specific mutation found in the individual patient [14]. Ehrhart et al have already demonstrated the power of integrating different databases to retrieve links between genetic variants and phenotypes in the cases of a rare disease for which a limited amount of data is available in a single place [15]. Being able to look at alternative targets that are a part of the sequence of developments that lead to disorders such as Rett may end up helping us to expand the knowledge about alternative causes and treatment opportunities.…”
Section: Introductionmentioning
confidence: 99%